Senegal - Education Pilot in Support of Female Literacy - Watkins, Sharon (World Bank, Washington, DC, 2012)
The aim of the Senegal Pilot Female Literacy Project was to raise the literacy rates of populations in Dakar and the more developed areas and, most importantly, to remote areas that cannot be reached via traditional mass literacy campaigns. The pilot, begun in 1995 and concluded in 2000, was designed to support the Senegalese government in strengthening efforts through partnership with other groups to raise national literacy rates, particularly for women, beyond the currently stagnant pre-pilot levels of approximately 40 percent. This was to offset the failure of traditional mass literacy campaigns instituted since the 1960s-programs which were only in the French language, not well-adapted to the local situation, and characterized by a lack of post-literacy reading materials. The broad development objectives of the pilot were to (a) improve education sector goals by providing literacy to both urban and rural populations, (b) raise literacy rates beyond current levels, especially for women, (c) to empower local women with the capacity to improve their standard of living through providing them with relevant skills through education and (d) strengthen the enabling environment for primary school education.